The fictional romantic sensibilities of Nelson Rodrigues in Rio de Janeiro as pessimism of the present (Ágora Journal, 2023)
ABSTRACT: The objective of this article is centered on perceiving, through the field of multifaceted sensibilities of Nelson Rodrigues (1912-1980), his romantic vision of the world, of Rio de Janeiro, and of love relationships in the course of the 20th century, when he produced his theatrical plays, journalistic production and other writings, perceiving a feeling of nostalgia for the past to the detriment of pessimism in the present. There is a redefinition of public spaces from the perspective of leisure and entertainment, and the assimilation by subjects of modern values coming from the bourgeois family, and the reproduction of these same values in other social classes. It is intended to decode the singularity, and the multifaceted desire for critical reflection of modernity in his writing, and of himself, and the subtleties when polemicizing about a conception of society that was expected, but which, on the other hand, did not materialize, by seeing the world around you changes constantly. It is intended to perceive as a methodology for analyzing the sources of attractions and signs through the evidence paradigm, aspects pursued by the author in his writing, and coming from his personality. As a theoretical reference I use the History of sensibilities in the diagnosis of ways of feeling and being present in the city, capturing through the sensitive dimension the whirlwind of changes in Rio society, and deciphering everyday life through the lens of fiction generated in a kaleidoscope of sensations.
Keywords: sensibilities; fiction; city